Pendidikan Karakter Melalui Keseniaan Sisingaan - Intan Dwiyanti; Andina Aisyah Eka Jati; Weby Khamelia; Dede Wahyudin; Jennyta Caturiasari (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
Character education is an effort that can be made consciously to shape abilities and personality in realizing virtuous behavior, attitudes, thoughts in carrying out social life. In this era of globalization, the character that appears in students is influenced by globalization itself. In the context of character education, Sisingan art can be used as a means of character education for students. Sisin art is an art originating from Subang Regency. The aim of this research is to find out character education through Sisingaan art in Subang. This study uses a qualitative descriptive method, data obtained from literature review or literature review. Character cultivation can be done in the local content of Sisingaan art. The Sisingaan Arts Local Content Curriculum introduces students to more familiarity with the natural, cultural and social environment. There are several values that can be developed, namely hard work, cooperation, togetherness, unity, creativity, harmony, harmony, and so on.